Novel mutations of CLCN7 cause autosomal dominant osteopetrosis type II (ADOII) and intermediate autosomal recessive osteopetrosis (ARO) in seven Chinese families. Issue 8 (17th November 2017) - Zhang, Xiaoya; Wei, Zhanying; He, Jinwei; Wang, Chun; Zhang, Zhenlin
ABSTRACT: Objectives : Defects in the chloride channel 7 ( CLCN7 ) gene lead to autosomal dominant osteopetrosis type II (ADOII, OPTA2 MIM 166600) and autosomal recessive osteopetrosis, autosomal recessive 4 (ARO, OPTB4 MIM 611490). The objective of the present study was to expand the mutational spectrum and analyze the correlation between mutational sites and clinical phenotypes. Methods : Seven affected individuals from unrelated Chinese families were clinically examined. X-ray examination and biochemical markers were evaluated. The 25 exons of CLCN7 and exon-intron boundaries were amplified and analyzed; we also used μ-CT to distinguish the features of sclerotic bone from the great trochanter of Pt 6 using the bones of unaffected subject in vitro . Results : We identified six cases of OPTA2 and one case of OPTB4. One OPTA2 patient displaying life-threatening symptoms died, and the OPTB4 patient presenting a relatively mild clinical course survived. We identified eight different CLCN7 mutations, including three novel mutations (p.G240E, p.F318S, and p.S753W), and μ-CT analysis showed that the volumetric bone mineral density, total porosity and open porosity of sclerotic bone were higher than the control. Conclusions : The present study revealed three novel mutations, showed the dense but brittle sclerotic bones of an OPTA2 patient, characterized OPTA2 symptoms from benign to fatal and reported a rare intermediate case of ARO in a Chinese population.